Hungarian Innovation Policy What's the Best Way Forward? - Hemmings, Philip (OECD Publishing, 2005)
The Hungarian government has recently been focusing on innovation policy as part of a wider campaign to improve the business environment. This paper first underscores the importance of a good general business climate in encouraging both formal and informal R&D activity as well as ensuring Hungary benefits from the international diffusion of innovation. In examining specific innovation policies, the new National Innovation System is described and an assessment is made of the National Innovation Fund and the Innovation Contribution used to fund it. Assessment of changes in R&D tax allowances and in the strategy for giving out grants for research is also made. The paper also looks at regulatory reform to improve industry-science links, including the government's recent legislative changes that make it easier for universities to set up spin-off companies. The final section considers what further reforms are needed to help tertiary and compulsory education become more conducive to innovation and to encourage the deepening of human capital in general
Keywords: Economics; Hungary